Предмет: Алгебра, автор: usenovagata

Сократите дробь
mn-pk+mk-pn
--------------------
pk^2-pn^2

Ответы

Автор ответа: Diana234558
1

Ответ:

mn - pk + mk - pn / pk^2 - pn^2 = m - p / kp - np


vityamath: ??
Автор ответа: animewnica202
2

Ответ:

 \frac{mn - pk + mk - pn}{pk {}^{2} - pn {}^{2} }  =  \frac{mn  + mk - pk - pn}{p(k {}^{2} - n {}^{2}  )}  =  \frac{m(n + k) - p(k + n)}{p(k - n)(k + n)}  =  \frac{(m - p)(k + n)}{p(k - n)(k + n)}  =  \frac{m - p}{p(k - n)}  =  \frac{m - p}{pk - pn}

Похожие вопросы